Randomized Placebo-Controlled Trial of Ferric Carboxymaltose in Heart Failure With Iron Deficiency: Rationale and Design. (May 2021) - Mentz, Robert J.; Ambrosy, Andrew P.; Ezekowitz, Justin A.; Lewis, Gregory D.; Butler, Javed; Wong, Yee Weng; De Pasquale, Carmine G.; Troughton, Richard W.; O'Meara, Eileen; Rockhold, Frank W.; Garg, Jyostna; Samsky, Marc D.; et al.
Abstract : Background: Iron deficiency (ID) has a prevalence of ≈40% to 50% among patients in heart failure (HF) with reduced ejection fraction and is associated with worse prognosis. Several trials demonstrated that intravenous ferric carboxymaltose leads to early and sustained improvement in patient-reported outcomes and functional capacity in patients with HF with reduced ejection fraction with ID, yet morbidity and mortality data are limited. Methods: The objective of the HEART-FID trial (Ferric Carboxymaltose in Heart Failure With Iron Deficiency) is to assess efficacy and safety of ferric carboxymaltose compared with placebo as treatment for symptomatic HF with reduced ejection fraction with ID. HEART-FID is a multicenter, randomized, double-blind, placebo-controlled trial enrolling ≈3014 patients at ≈300 international centers. Eligible patients are aged ≥18 years in stable chronic HF with New York Heart Association functional class II to IV symptoms, ejection fraction ⩽40%, ID (ferritin <100 ng/mL or ferritin 100–300 ng/mL with a transferrin saturation <20%), and documented HF hospitalization or elevated N-terminal pro-brain natriuretic peptide. Consented patients are assigned to ferric carboxymaltose or placebo at baseline, with repeated visits/assessments every 6 months for additional study drug based on hemoglobin and iron indices for the trial duration. The primary end point is a hierarchical composite of death and HF hospitalization at 12 months and change from baseline to 6 months in the 6-minute walk test distance. Conclusions: The HEART-FID trial will inform clinical practice by clarifying the role of long-term treatment with intravenous ferric carboxymaltose, added to usual care, in ambulatory patients with symptomatic HF with reduced ejection fraction with ID. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03037931. Abstract : Supplemental Digital Content is available in the text.